A coaching perspective of the sport and exercise sciences. Suggestions on how sport scientists can enhance the coach-sport scientist relationship - Kirkland, A.; Webb, V. (The Sport and Exercise Scientist, 2015)
In performance sport there should always be one ultimate aim, to enhance performance. This aim provides clarity in purpose to athletes, coaches, programme managers and support professionals and simplifies the decision-making processes: For example, by asking the question "Is what we`re doing contributing to the ultimate aim?" If the answer is no, then there is little point in doing it.